Lexin: Audio files, Swedish dictionary - Lexin: Sound Files, Swedish Dictionary - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Audio files with pronunciation of entries in the Swedish Lexin dictionary.

Ljudfiler med uttal av uppslagsorden i Lexin svenskt lexikon.
Lexin: Ljudfiler, svenskt lexikon
Keywords: lexicon; lexikon; lexin; lexin; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur